2003
DOI: 10.1002/eji.200324461
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of peptide presentation by major histocompatibility complex class II molecules at the surface of macrophages

Abstract: We studied major histocompatibility complex class II-dependent presentation of two T cell epitopes delivered as synthetic peptides by fixed macrophages. Treatment of bone marrow macrophages with inhibitors of proteinases of the metallo-, aspartic and serine proteinase families enhanced presentation of peptides, indicating that several enzyme families participate in destructive antigen processing of exogenous peptides. High performance liquid chromatography and mass spectrometry analysis demonstrated the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 56 publications
(82 reference statements)
3
14
0
Order By: Relevance
“…To test antigen presentation of CII digests, 40-l aliquots of each digest were added to fixed THP-1 cells in the presence of the same doses of the enzyme inhibitors PMSF, E-64d, pepstatin, and phenanthroline to prevent further degradation (35) and then incubated for 18 hours at 37°C. To localize peptide/DR1 complexes in subcellular fractions, vesicular compartments present in the Percoll gradient fractions were added to 96-well plates and tested with T cell hybridomas.…”
Section: Methodsmentioning
confidence: 99%
“…To test antigen presentation of CII digests, 40-l aliquots of each digest were added to fixed THP-1 cells in the presence of the same doses of the enzyme inhibitors PMSF, E-64d, pepstatin, and phenanthroline to prevent further degradation (35) and then incubated for 18 hours at 37°C. To localize peptide/DR1 complexes in subcellular fractions, vesicular compartments present in the Percoll gradient fractions were added to 96-well plates and tested with T cell hybridomas.…”
Section: Methodsmentioning
confidence: 99%
“…Purified MHC‐II molecules have been shown to bind peptides containing T‐cell epitopes and partially to protect them from degradation by exogenously added proteolytic enzymes, such as cathepsin B, pronase E and chymotrypsin, for presentation to CD4 T cells in cell‐free systems, 20,21 although the factors influencing the rescue of exogenous peptides by MHC‐II expressed at the cell‐surface of APC for presentation to CD4 T cells are not well understood. In our previous study we showed that enzymes of the metallo‐, aspartic‐ and serine‐proteinase families are involved in destructive processing of exogenous peptides at the surface of macrophages 22 . In this report, we show that binding to MHC‐II molecules at the surface of APC may protect a significant proportion of exogenous peptides from proteolytic degradation.…”
Section: Introductionmentioning
confidence: 56%
“…Macrophages were fixed with 1·0% paraformaldehyde (w/v in Hanks' balanced salt solution; HBSS) for 4 min to block antigen internalization. This treatment has been previously shown to preserve cell surface‐associated enzyme activity without exposing lysosomal enzymes 17,22 . To test the effect of pH on peptide presentation, HBSS pH 7·2; and 0·1 m sodium citrate buffers with pH 6·5 and pH 5·5 were used.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the incubation time, 30 ml aliquots of the reaction mixture were transferred to 96-well plates containing 4 Â 10 4 /well prefixed macrophages in 0.1 M Na-citrate buffer (pH 5.5) supplemented with the following broad-spectrum enzyme inhibitors to block further processing [21]: pepstatin A (inhibitor of aspartic proteinases, 0.5 mM [22]), 1,10-phenanthroline (inhibitor of metalloproteinases, 0.1 mM [23]), phenylmethylsulfonyl fluoride (inhibitor of serine proteinases, 3.0 mM [24]) and E-64d (inhibitor of cysteine proteinases, 10 mM [25]). Following 18 h incubation, plates were washed to remove inhibitors and digests, and specific T-cell hybridomas were added in 200 ml culture medium (4 Â 10 4 /well).…”
Section: After Incubation At 37mentioning
confidence: 99%
“…Productive processing of peptide epitopes that directly load MHC-II molecules for presentation to CD4 T cells was assessed by incubation of digests with prefixed macrophages in the presence of enzyme inhibitors to prevent further degradation by surface enzymes [21]. rPA digested by two regions of the gradient (fractions 4-7 and 24-28) was presented to a T-cell hybridoma specific for the epitope PA 547À560 (Fig.…”
Section: Localization Of Antigen-processing Activity In Subcellular Fmentioning
confidence: 99%